Audit of provincial IVIG Request Forms and efficacy documentation in four Ontario tertiary care centres. Issue 2 (31st January 2017) - Shih, A. W.; Jamula, E.; Diep, C.; Lin, Y.; Armali, C.; Heddle, N. M.; Traore, A.; Doherty, J.; Shah, N.; Hillis, C. M.
SUMMARY: Objective: Retrospective audit of IVIG Request Forms in four Ontario tertiary care centres: to determine the case mix of new IVIG requests, to authenticate information provided, and to determine documentation of clinical efficacy. Aims: To understand contributors to increases in IVIG utilisation and to determine whether IVIG is being used and monitored appropriately. Introduction: Intravenous immunoglobulin (IVIG) use in Canada is high compared with other developed countries. We performed a retrospective audit of new IVIG Request Forms across four tertiary care centres in Ontario, one with an active surveillance programme, to determine the case mix, authenticate information provided and assess documentation of efficacy. Methods: Consecutive adult patients with a first‐time IVIG request in 2014 were included. The ordering physician specialty, form completeness, documentation of diagnostic criteria for the medical condition and indication for IVIG use and documentation of efficacy were assessed by form and chart review. Results: Of 178 patients, the most common indications for IVIG were immune thrombocytopenia (24.2%) and secondary immune deficiency (20.2%). The most frequent prescribers were haematologists (37.6%) and neurologists (10.7%). Other conditions not listed on the form represented 24.2% of cases, with most not indicated in current guidelines. A total of 32.6% of cases overall lacked verification of diagnostic criteria and 51.7% lacked verification for IVIG utilisation criteria, with the number of cases meeting criteria based on documentation being higher at the active surveillance site ( P = 0.005). A total of 19.1% of cases had a discrepancy between the indication written on the form and the documented clinical diagnosis. A total of 18.7% of clinic notes following IVIG had no mention of efficacy. Conclusion: Our audit demonstrates a lack of compliance with IVIG Request Form requirements, a lack of documentation of diagnostic criteria and efficacy, and suggests inappropriate use of IVIG. Current implementation of the form may not be sufficient as a strategy for improving appropriate IVIG use.